Qualitative Investigation of the Cooking with Kids Program: Focus Group Interviews with Fourth-Grade Students, Teachers, and Food Educators - Lukas, Catherine V.; Cunningham-Sabo, Leslie (Journal of nutrition education and behavior, 2011)
Focus group (FG) interviews with students and adults were used to obtain a rich understanding of the Cooking with Kids classroom experience from the child and adult participant perspectives. FG topics included students' cooking experiences at school and home and perceptions of Cooking with Kids. Verified transcripts of recorded interviews were entered into NVivo, coded for themes, and confirmed through intercoder reliability. Twenty-two FGs were conducted with fourth-grade students (n = 178), 3 FG with teachers (n = 17), and 1 FG with 5 Cooking with Kids food educators. Students in cooking interventions described positive experiences with curriculum integration into academic subjects and were more likely to consider classmates friends. FG revealed student perspectives to strengthen content and implementation of experiential foods programs. This study provides an example of how qualitative methods can add “student voice” to evaluation of school-based programs.